Preventive Efforts of the Women's Empowerment and Child Protection Service in Addressing Cases of Sexual Violence Against Children - Djamaluddin, Musdalifa; Paweni, Lisnawati; Bilondatu, Nikma; Nuna, Muten; Tabo, Sarfan (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the preventive efforts carried out by the Department of Women’s Empowerment and Child Protection (DP3A) of Gorontalo Regency in addressing cases of child sexual violence, as well as to identify the challenges encountered during the implementation of these programs. This research employed a qualitative approach using observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that DP3A has implemented several preventive strategies, including school- and community-based sexual education programs, public awareness campaigns, and basic parental training. DP3A also performs a coordinating role in providing rehabilitative and reintegrative interventions for child perpetrators through cross-sectoral collaboration. However, significant challenges remain, including limited human resources and facilities, suboptimal inter-agency coordination, low public awareness, and insufficient involvement of supporting institutions. The study concludes that although DP3A’s preventive efforts are moderately effective, they are not yet comprehensive due to institutional capacity constraints. Strengthening resources, developing an integrated coordination system, and enhancing community participation are essential to creating a safer environment for children in Gorontalo Regency.